Dedifferentiated Liposarcoma of the Retroperitoneum With Hyperleukocytosis as Paraneoplastic Syndrome: A Rare Presentation - Sangita S Mehta; Rajeshwari K Muthusamy; Firoz Rajan; Shobhanaa P. S. (MAMC Journal of Medical Sciences, 2019)
Background: Paraneoplastic syndrome is a clinical syndrome with systemic effects, triggered by altered immune response to a neoplasm. Paraneoplastic syndrome was described mostly in association with epithelial malignancies, while in a soft tissue sarcoma it is unusual and hyperleucocytosis as a paraneoplastic phenomenon is very rare. Case presentation: We report a middle aged male patient with bilateral retroperitoneal masses with histomorphology of myxoid liposarcoma with dedifferentiation. Hyper-leucocytosis in the peripheral blood and pronounced myeloid hyperplasia in marrow was found with no obvious focus of infection. There was gradual reduction in white cell count in the postoperative period and reached normal values on Day 8. Hence a diagnosis of dedifferentiated liposarcoma of the retroperitoneum with hyperleucocytosis as a paraneoplastic manifestation was made. Conclusion: Paraneoplastic manifestation could probably be due to production of G-CSF by tumor cells as the leucocytosis disappeared after tumor resection. Further, leucocytosis is not reported in association with well differentiated liposarcoma, and if happens to be so, it might be a clue to search for the dedifferentiated component.